Long-term Complications of Female Genital Mutilation - Clitoral Epidermoid Inclusion Cyst - Hilal Aktürk; Mustafa Cengiz Dura; Berk Gürsoy; Waseem Alsalamin; Selma Ermin (Bagcilar Medical Bulletin, 2024)
This case study critically examines the long-term detrimental effects of female genital mutilation (FGM), specifically focusing on the development of clitoral epidermoid inclusion cysts. The study illuminates the often-overlooked post-mutilation complications that extend beyond immediate physical trauma, encompassing significant anatomical alterations with potential psychosocial implications. As a direct consequence of FGM, clitoral epidermoid inclusion cysts represent a physical manifestation of such prolonged complications, contributing to discomfort, potential sexual dysfunction, and an overall decline in quality of life. In an unusual case, a 38-year-old African woman presented with a painful clitoral tumor intermittently draining for three years. The study underscores the urgent need for comprehensive preventive measures, early diagnosis, and effective management strategies in affected populations to mitigate the enduring consequences of this harmful practice.